2021
DOI: 10.1097/jom.0000000000002299
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Home-Based Telework and Work Engagement During the COVID-19 Pandemic

Abstract: Objective: The present study examined the relationship between the intensity of home-based telework and work engagement. Methods: This cross-sectional study using a self-administrated questionnaire survey was conducted from December 22 to 25, 2020, in Japan. The subjects were asked single-item questions about the intensity of telework and three-item questions about work engagement using the Utrecht Work Engagement Scale. Coefficients were estimated using a multilevel regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
1
21
0
2
Order By: Relevance
“…To our knowledge, no empirical studies have examined the effects of teleworking specifically on both employees' work engagement and intention to quit during the COVID-19 pandemic. One study established that high-quality telework (e.g., agile workplaces, virtual leadership) was associated with higher work engagement during the pandemic [38]; however, different results were obtained in a study conducted by [39], which found that high intensity telework was not associated with work engagement during the pandemic. We were also able to locate a study that concluded that among employees who worked from home during the COVID-19 pandemic in Japan, an increase in sleep hours, effective interactions with supervisors, and working less than 40 hours a week were associated with high work engagement [8].…”
Section: The Role Of Teleworkingmentioning
confidence: 97%
“…To our knowledge, no empirical studies have examined the effects of teleworking specifically on both employees' work engagement and intention to quit during the COVID-19 pandemic. One study established that high-quality telework (e.g., agile workplaces, virtual leadership) was associated with higher work engagement during the pandemic [38]; however, different results were obtained in a study conducted by [39], which found that high intensity telework was not associated with work engagement during the pandemic. We were also able to locate a study that concluded that among employees who worked from home during the COVID-19 pandemic in Japan, an increase in sleep hours, effective interactions with supervisors, and working less than 40 hours a week were associated with high work engagement [8].…”
Section: The Role Of Teleworkingmentioning
confidence: 97%
“…34,35,54 However researches on work engagement is scarce. 29,32 This study explores the relationship between home-based telework and work engagement during the COVID-19 pandemic. The findings will enrich the literature on home-based work and work engagement.…”
Section: Conclusion Theoretical Contributionsmentioning
confidence: 99%
“…A cross-sectional analysis of the data from this project showed that high-frequency WFH (≥4 days per week) was associated with high job control and low subjective psychological stress in the early stages of the COVID-19 epidemic (Ikegami et al, 2022 ). However, those with medium-frequency WFH (WFH for 2–3 days per week) or low-frequency WFH (WFH between 1 d per week and 1 d per month) had higher work engagement compared to those who worked exclusively in the workplace (Nagata et al, 2021b ). In these cross-sectional studies, WFH was suggested to be associated with good mental health among workers.…”
Section: Introductionmentioning
confidence: 99%